Effects of increased planting density and reduced nitrogen application on rice lodging resistance yield and quality - Diankai Gong; Yi Wang; Ying Chen; Xianping Liu; Guangxing Yu (Scientific Reports)
Abstract With the increasing demand for resource conservation and environmental protection in agricultural production, increasing density and reducing nitrogen application have emerged as an important direction in rice cultivation. Optimizing cultivation practices can ensure stable yield increases and improvement of rice quality while reducing nitrogen fertilizer input. This study aimed to investigate the effects of density-increasing and nitrogen-saving (DINS) practices on lodging resistance, yield, and quality of rice, providing a scientific basis for high-yield and efficient rice cultivation. The field experiment was conducted at the Liaoning Rice Research Institute’s experimental base from 2020 to 2021, using the upright-panicle rice variety Liaojing 212. Two transplanting densities (D1: 30 cm × 16.6 cm and D2: 25 cm × 12 cm) and two nitrogen application levels (F1: conventional nitrogen application rate of 225 kg N/ha and F2: 190 kg N/ha) were set. By measuring plant type, panicle structure, stem composition and mechanical properties, yield components, and rice quality, the impacts of DINS on lodging resistance, quality, and yield were analyzed. Results showed that compared to conventional planting, DINS reduced rice yield by 1.63–3.66%, but the difference was not significant. DINS compensated for the yield reduction caused by a 15% reduction in nitrogen fertilizer through a 7.78–8.09% increase in total effective panicles. However, DINS significantly reduced lodging indices of the N1, N2, and N3 stem internodes by 18.63–33.23%, 26.79–36.77%, and 27.06–31.93%, respectively, significantly enhancing lodging resistance. This was mainly achieved by reducing plant height and center of gravity, and increasing lignin and cellulose content in the stems. Rice eating quality was significantly improved by 9.78–10.34%, mainly through reductions in amylose and protein content in the grains. DINS can ensure stable rice yield while significantly improving lodging resistance and eating quality, with notable economic and environmental benefits, providing a new approach for high-yield, high-efficiency, and high-quality rice cultivation.